Genomic amplification of the human telomerase gene (hTERC) associated with human papillomavirus is related to the progression of uterine cervical dysplasia to invasive cancer - Liu Hongqian; Liu Shanling; Wang He; Xie Xiaoyan; Chen Xinlian; Zhang Xuemei; Zhang Youcheng (BMC, 2012)
Abstract Background Human papillomavirus (HPV) infection plays an etiological role in the development of cervical dysplasia and cancer. Amplification of human telomerase gene (hTERC) and over expression of telomerase were found to be associated with cervical tumorigenesis. This study was performed to analyze genomic amplification of hTERC gene, telomerase activity in association with HPV infection in different stages of cervical intraepithelial neoplasia (CIN) and cervical cancer. We were studying the role of hTERC in the progression of uterine cervical dysplasia to invasive cancer, and proposed an adjunct method for cervical cancer screening. Methods Exfoliated cervical cells were collected from 114 patients with non neoplastic lesion (NNL, n=27), cervical intraepithelial neoplasia (CIN1, n=26, CIN2, n=16, CIN3, n=24) and cervical carcinoma (CA, n=21), and analyzed for amplification of hTERC with two-color fluorescence in situ hybridization (FISH) probe and HPV-DNA with Hybrid Capture 2. From these patients, 53 were taken biopsy to analyze telomerase activity by telomeric repeat amplification protocol (TRAP) and expression of human telomerase reverse transcriptase (hTERT), with immunohistochemistry (IHC). All biopsies were clinically confirmed by phathologists. Results Amplification of hTERC was significantly associated with the histologic diagnoses (p<0.05). The positive correlation was found between the level of hTERC amplification and histologic grading of dysplasia (CIN2/3 from CIN1 or normal, P=0.03). A profounding increase in the accumulation of HPV and hTERC positive cases was observed in the CIN3 subgroup compared with the CIN2 group, 25% versus 62.96%, respectively (p=0.007). Conclusions hTERC ampliffication can be detected with FISH technique on exfoliated cervical cells. Amplification of hTERC and HPV infection are associated with more progressive CIN3 and CA. The testing of hTERC amplification might be a supplementary to cytology screening and HPV test, especially high-risk patients. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1857134686755648.